2020
DOI: 10.35759/jabs.148.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of Rhizophagus irregularis strain on cassava root development and Phosphorus uptake under acidic soils conditions of Walungu territory, Eastern DR Congo.

Abstract: Objective: In the highlands of South-Kivu province of DR Congo, cassava is grown on marginal land not suitable for other crops. Walungu territory for instance is dominated by acidic soils and has the highest nutrient depletion rate in the country. On such types of soil, nutrient depletion is accompanied by a decrease in the availability of phosphorus and many other nutrients. The use of Arbuscular mycorrhizal fungi (AMF) would therefore be an alternative to improve the phosphate nutrition of cassava under diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similarly, several researchers documented the beneficial impact of mycorrhizae on cassava plants with nutrient intake [8,[19][20][21][22]. For instance, AMF's contribution to Phosphate uptake was examined by Ndeko et al [23]. They discovered that using AMF is suitable for enhancing cassava's phosphate nutrition in various soil types.…”
Section: The Function Of Arbuscular Mycorrhizal Fungi In Soil Nutrien...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, several researchers documented the beneficial impact of mycorrhizae on cassava plants with nutrient intake [8,[19][20][21][22]. For instance, AMF's contribution to Phosphate uptake was examined by Ndeko et al [23]. They discovered that using AMF is suitable for enhancing cassava's phosphate nutrition in various soil types.…”
Section: The Function Of Arbuscular Mycorrhizal Fungi In Soil Nutrien...mentioning
confidence: 99%
“…However, following AMF inoculation in unsterilized soil, the root dry weight dropped. They concluded that the Rhizophagus iregularis strain, particularly when the soil is not treated with phosphorus, increases the Phosphate uptake of the cassava plants [23].…”
Section: The Function Of Arbuscular Mycorrhizal Fungi In Soil Nutrien...mentioning
confidence: 99%